TREATMENT OF DEPRESSIVE AND ANXIETY DISORDERS DURING PREGNANCY AND LACTATION: A CASE STUDY - Inić, Teodora; Cvjetković Bošnjak , Mina; Kuljančić , Dušan (Sanamed, 2024)
Introduction:Depressive and anxiety disorders are among the most common psychiatric conditions, as stated by the WHO in 2015. These disorders often manifest during adolescence or young adulthood, making it unsurprising for women in pregnancy or lactation periods to experience either a first manifestation or a recurrence of symptoms. When these disorders occur during pregnancy or lactation, antidepressant treatment may be required per established protocols. However, concerns often arise among patients, such as: “Is this medication safe for me and my baby? Could it negatively affect my baby’s development?” These hesitations can sometimes extend to healthcare providers if they lack adequate education on the topic. Therapeutic guidelines worldwide recommend psychotherapy for mild symptoms, whereas pharmacotherapy, often combined with psychotherapy, is carefully considered for moderate symptoms. Case Report: This paper presents three case studies of pregnant women with depressive and anxiety disorders. The first case involves a patient with prenatal depression who achieved complete remission after starting antidepressant therapy. The second case highlights the recurrence of symptoms following the discontinuation of psychopharmaceuticals. The third case emphasizes the importance of individualized treatment plans and illustrates the recurrence of symptoms in a patient previously in remission. Conclusion: Pregnant women with mental health challenges often have significant concerns about using psychopharmaceuticals during pregnancy. This paper aims to underscore that the appropriate selection and dosage of antidepressant medications can lead to remission of disorders without adverse effects on either the mother or child.